Heat Transfer and Fluid Flow in a Double Pipe Heat Exchanger, Part I: Experimental Investigation - Kotian, Shreyas; Methekar, Nachiket; Jain, Nishant; Naik, Pritish (Asian Review of Mechanical Engineering, 2020)
Double pipe heat exchangers have assumed importance over the years owing to their simple construction, ease of maintenance and cleaning, and extensive use in applications involving sensible heating or cooling of process fluids. In this present study, a detailed comparison is made between the theoretical results and experimental data of the performance parameters of the heat exchanger. Experiments were performed for 60 ≤ Re ≤ 240 for two different inlet temperatures of the hot fluid, 50°C, and 70°C keeping the inlet temperature of the cold fluid constant at 31°C. Graphs were plotted between various performance parameters such as overall heat transfer coefficient, effectiveness, NTU, outlet temperatures of the hot and cold streams against mass flow rates of the fluid. Lastly, a comparison was done between the theoretical data and experimental results and they showed good accordance with a mean deviation of 10-12%.